LA MATERIATHEQUE DU SERVICE DE DEVELOPPEMENT DU MATERIEL EET DES PROGRAMMES D'ENSEIGNMENT ET DE REEDUCATION, OU COMMENT REALISER UNE BIBLIOTHEQUE D'OUTILS: )THE INSTRUCTIONAL MATERIALS CENTER OF THE SERVICE FOR THE DEVELOPMENT OF SPECIAL EDUCATION MATERIALS AND PROGRAMS, OR HOW TO ORGANIZE A LIBRARY OF EDUCATIONAL TOOLS - Dubuc, Pierrett (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF